Filicide-Parasuicide: A Case Report and ‘Insight’ (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Filicide is a tragic crime of murdering one’s own child. This article describes a case of murder followed by suicide attempt by the mother. Examining this type of offender may help us better understand the group who complete murder followed by suicide. Present case is being reported with an attempt to evaluate the episode so that preventive measures could be adopted. Previous research has found that the offending parents are commonly depressed and that suicide is often associated as an actual act or an intention.
Keywords: Filicide; Suicide; Depressive disorder forensic psychiatry; Familicide; Postmortem; Infanticide